Effect of Ivabradine on Endothelial Function in Patients with Stable Angina Pectoris: Assessment with the Endo-PAT 2000 Device. Issue 10 (October 2015) - Jedlickova, Lucia; Merkovska, Lucia; Jackova, Lucia; Janicko, Martin; Fedacko, Jan; Novakova, Bozena; Chmelarova, Anna; Majernik, Jaroslav; Pella, Daniel
Abstract Introduction Ivabradine has opened up new possibilities for treating stable angina and chronic heart failure by lowering heart rate. Ivabradine lowers heart rate by selectively inhibiting theI f current in the sinoatrial node. This study aimed to determine whether the decrease in heart rate achieved with ivabradine was accompanied by hemodynamic changes that might lead to an enhancement of endothelial function. Methods Thirty patients with stable angina pectoris were included in the study. Ivabradine (5 mg bid) was added to the recommended standard treatment. Endothelial function was assessed at baseline and after 3 months of ivabradine therapy, with an Endo-PAT 2000 device (Itamar Medical, Israel). This device was recently developed for the noninvasive assessment for endothelial dysfunction. We evaluated reactive hyperemia index (RHI), which reflects endothelial function, and augmentation index (AI), which provides an indication of arterial stiffness. Results The study population consisted of 25 (83.3%) men and five (16.7%) women. The mean age of the patients was 65.4 ± 6.7 years. Twenty-eight (93.3%) patients had a history of myocardial infarction (ST-segment elevation myocardial infarction or non-ST-segment elevation myocardial infarction), 23 (76.6%) had undergone revascularization (percutaneous coronary intervention or coronary artery bypass graft), 16 (53.3%) had type 2 diabetes mellitus, and 29 (96.6%) had arterial hypertension. The mean resting heart rate decreased significantly, from 77 ± 7 bpm at the start of the study to 65 ± 6 bpm after treatment (P  < 0.0001). Endothelial function was found to have improved significantly after 3 months of ivabradine therapy. Mean RHI before treatment was 1.54 ± 0.30, suggesting probable endothelial dysfunction, whereas mean RHI at the end of the study was 1.83 ± 0.36 (P  < 0.0001). AI also improved significantly on treatment, from 21 ± 20% to 10 ± 21% (P  < 0.0001). Conclusion The addition of ivabradine to the treatment regimen of patients with stable angina pectoris both lowered heart rate and improved endothelial function. However, broader, randomized, double-blind, placebo-controlled clinical trials are required to confirm these findings. Funding Sponsorship for this study was funded by a VEGA grant no. 1/0858/11. Article processing charges were funded by Servier.